Spectral method for bending analysis of rectangular functionally graded plates - Hammou Amina; Hilali Youssef; Mesmoudi Said; Boujmal Radouane; Askour Omar; Bourihane Oussama (E3S Web of Conferences)
This study investigates the bending behavior of functionally graded rectangular plates using the spectral collocation method to offer precise modeling. We apply the First-order Shear Deformation Theory (FSDT) to accurately capture the effects of shear deformation in our plate behavior models. The effectiveness of the proposed method is demonstrated by a comparison of the results obtained with those of literature.